MEMBANGUN SMARTAPARATUR SIPIL NEGARA (ASN) MENUJU BIROKRASI BERKELAS DUNIA TAHUN 2024 - Hasan, Erliana (Fakultas Politik Pemerintahan, 2019)
Building Smart State Civil Apparatus Towards World Class Bureaucracy in 2024. The purpose of this study is to find out the development of apparatus resources through orientation, empowerment, education and training and develop influencing factors to build smart state civil apparatus towards world-class bureaucracy. In this study, the author uses a type of descriptive research, namely research that presents and aims to provide an overview and explanation of the variables under study. Data analysis techniques used the techniques of Maththew B. Miles and Michael Huberman, (2007: 16), which consisted of 4 components: data collection: data reduction, presentation and conclusion. The results show that: (1) the State Civil Apparatus must master technology, and even be able to engineer various applications for information services to the public; (2) having a sense of nationalism and being able to implement general principles of good governance; (3) have a sense of empathy and responsibility; (4) necessary supporting factors in developing apparatus resources in a sustainable and comprehensive manner; (5) able to formulate a vision and values that can redesign work for selection and assessment in conducting placements in accordance with the implementation of a performance management system.